Multi-stage planning and calculation method of power system considering energy storage selection - Yang, Guoshan; Liu, Xumin; Zhang, Wei; Ma, Zhengxiong (Journal of physics. Conference series, 2024)
Under new power system flexibility, this text proposes a multi-stage random generation-transmission-energy storage, integrated programming method that considers the short-period flexibility demand. The model can accurately reflect the relationship between short-period operation and long-period uncertainty within an extraordinary method and can also correctly evaluate the value of investment flexibility. Based on this, this text proposes a parallel processing solution, which can be separated into subproblems through column generation and shared decomposition and enables simulation calculation using a distributed measuring platform in long-period programming. The calculation proves the optimal solution speed of the proposed method and can effectively solve problems that cannot be dealt with by the known methods.